Effects of PET microplastics on the physiology of Drosophila. (November 2021) - Shen, Jie; Liang, Boying; Zhang, Dake; Li, Yan; Tang, Hao; Zhong, Lichao; Xu, Yifan
Abstract: Microplastics, as a new type of pollution, have attracted global attention and have become a research focus in recent years. Given the small size of microplastics, they can be ingested by many organisms. In addition, microplastics can enter the human body through the food chain. So, the potential dangers of microplastics can't be ignored. This study took Drosophila as a model organism to delve the physiological effects of polyethylene terephthalate microplastics (PET-MPs). Here, we reported that the higher concentration of PET-MPs was, the more obvious the effect became. The amount of oviposition decreased in female flies exposed, indicating that microplastics affected reproduction. PET-MPs caused the decrease of triglyceride and glucose content in male flies, as well as the decrease of starvation resistance, suggesting the effect of microplastics on energy metabolism. In addition, the 24-h spontaneous activity of flies exposed to PET-MPs increased significantly. The experimental results can help understand the potential impact of microplastics on physiology. Highlights: The higher the concentration of PET-MPs was, the more obvious impact on flies became . PET-MPs increased the spontaneous activity of flies for 24 h. PET-MPs reduced egg production in female flies. PET-MPs decreased lipid, glucose content and starvation resistance in male flies.